Estimation of the stress level on a cross section of a reinforced concrete beam via Acoustic emission Intensity Distribution (AID) analysis. (10th March 2018) - Liu, Simeng; Ma, Huixiang
Highlights: AE measurements are used to determine critical stress levels of concrete beams. The method exploits a correlation between stress and the relevant AE distributions. In tests, the method characterised the stress state with an error of about 5%. The idea of the method may work on structures made of concrete or similar materials. Abstract: Measuring stress is critical in the Civil Engineering. However, established acoustic emission-based techniques can hardly evaluate the stress level which a structure is experiencing. Accordingly, an idea of 'listening' to Acoustic Emission (AE) to evaluate critical stress states in reinforced concrete (RC) beams is investigated here. Previous work found that the stress diagram of an RC beam cross section strongly correlates with the corresponding AE event intensity distribution pattern. Therefore, the stress level of this type of structures was estimated by utilising the remarkable correlation in this study. First of all, the stress diagrams of a cross section of an RC beam loaded to failure were analysed, revealing features which had close relations with the stress level of the section. Thanks to the correlation, these features were also extracted from the corresponding distribution patterns of the AE event intensity and then used to estimate the stress state. As a result, the AE Intensity Distribution (AID) analysis approach was developed. Data from an experiment conducted on six RC beams with a Digital Image Correlation (DIC) system and an AE device were adopted to verify the approach. Results showed that the indicators of the approach strongly correlated with the stress levels of the specimens; that the approach can characterise the stress states precisely, with an error of about five per cent in critical stages. Besides the approach, more profound significance of this work lies in that it demonstrated the great capability of an innovative strategy, namely characterising structural behaviours accurately via correlating an AE distribution pattern with the corresponding stress diagram.